Financial Literacy Education for the Fisherman Community Group in Bengkulu City to Improve Financial Knowledge - Febzi Fiona; Yovita Agustina; Serly Apriansah (Universitas Lambung Mangkurat, 2024)
The rapid development of financial literacy has brought numerous benefits to the economic operations of both large and small-scale communities. When establishing a company, understanding how to manage finances is crucial. The population should possess basic financial knowledge, including financial technology (fintech) skills, as part of their financial literacy. Fintech has made borrowing money faster and easier. The objectives of this outreach are: 1) To enhance the financial literacy of the fisherman community regarding their financial management skills, enabling them to develop their businesses, and 2) To encourage the fisherman community to improve their financial intelligence. The implementation method used the Participatory Action Research (PAR) approach, oriented toward fishermen to provide input and solutions to their problems. The results of this outreach showed that a significant portion of the fisherman groups lacked a good understanding of finance and technology. Following this outreach, they better understood the importance of financial literacy.